Philosophical and Ishari Interpretation: Traces of Islamic Thought from the Golden Age to the Decline - Daniya, Salsabila Shofa; Hulumah, Siti Rohmah Tuwloh (UIN Sunan Gunung Djati Bandung, 2026)
The purpose of this study is to examine the meaning, history, and limitations of philosophical interpretation; the history of the emergence of philosophical interpretation during the golden age of Islam; the differences between philosophical interpretation and symbolic interpretation; and the history of the emergence of symbolic interpretation at the end of the golden age of Islam. The research method used in this study is library research, with a qualitative approach, aiming to produce descriptive data presented in narrative form. During the Abbasid Dynasty, which was the golden age of Islam at that time, many philosophical books from Greece, Persia, and India were translated, causing philosophical interpretation to develop rapidly from the 8th to the 12th century AD. Philosophical interpretation itself is an interpretation of the Quran using a philosophical approach, oriented towards reason and rationality based on philosophical principles, but with less attention paid to inner meaning. Meanwhile, at the end of the golden age of Islam, philosophical interpretation developed rapidly from the 12th to 14th centuries AD, emphasizing spiritual awareness during the decline of Islam.